FUNGICIDES ON SPRING WHEAT - V. A. Lavrinova; I. M. Evseeva (Зерновое хозяйство России, 2018)
The results of three-year use of fungicides in laboratory and in the field have been considered. The substantiation of their biological and economic efficiency against harmful diseases in Tambov region has been given. The application of fungicides, possessing a wide spectrum of activity, reduced pathogen infection on seeds and plants. During the years of study diseases of aerogenic origin prevailed, among them septoriosis (Septoria spp.) with 11,8-35,7% and wheat leaf rust (Puccinia triticina) with 27,6-72,5%. The influence of drought and heat upon spring winter seeds has been considered. As a result, the seeds received under these conditions possessed satisfactory literal and primary roots, purpose of which is to form element of productivity and preservation of future yields, their penetrating into subsoil layers and supplying plants with water and nutrients. The peculiarity of spring wheat cultivation is that it possesses weaker root system than winter wheat. Air temperature increase to 22-36°С in a vegetation period reduces all stages of growth, violates photosynthesis and decreases yield. Fungus р. Alternaria spp  is a dominant component of pathogens on spring wheat seeds, that accounts 60-83% under total infection of seeds during last years. Complex protection of the crop influenced positively on productivity and elements of its structure. Superiority of fungicides over a control variant was noted in a number of productive stems, number of seeds per spikelet, 1000 grain weight. Infection of spring wheat plants and seeds with pathogens depended upon application of fungicides and on climatic feature of crop growing.